Team of vipers : my 500 extraordinary days in the Trump White House - Sims, Cliff (Thomas Dunne Books, St. Martin's Press, 2019)
Offers a first-hand account of the author's time in the Trump White House, discussing the infighting and leaking he witnessed first-hand and his role in the president's successes and disasters.